Cultural Pastoral Accompanying Behavior Towards The Mrs. RS "Blame Yourself" (Self Blaming) - Simamora, Daud Marsahata (International Journal of Social Discussion, 2024)
People with major depressive disorder (MDD) are more susceptible to experiencing moral emotions related to self-blaming behavior, such as deep and deep-rooted guilt towards the person who experiences it. Moral emotions that have self-blaming behavior will influence the people around them. This is what happened to an elderly mother (Mrs, RS) when she lost the people she loved and left her forever (her husband died), and also the people she loved moved away from her (she was left alone and with her children). and his grandchildren stay away from him). In this section the author will discuss the potential influence of moral emotions that behave in a self-blaming manner, and "Cultural Pastoral Assistance for Hospital Mistresses who behave in a self-blaming manner." This was done with the aim of understanding and comprehending what self-blaming behavior really is, exploring the root of the problem of why self-blaming behavior occurs, as well as providing pastoral assistance in providing solutions for Mrs. Hospitals who experience self-blaming behavior.